Analytical review of contemporary speculative literature: Foresighting the future of health, energy, and economics within strategic pillars and the 2030 SDG framework - Alhomoud, Ghassan Nawaf Jaber; Ismail, Sayed M; Koka, Nisar Ahmad (Research Journal in Advanced Humanities, 2026)
This article argues that contemporary speculative literature operates as a mode of cultural foresight through which writers test, complicate, and ethically evaluate possible futures of health, energy, and economics. Rather than treating speculative fiction as a crude predictive machine, I read it as a literary practice of scenario-making that reveals hidden interdependencies between bodily vulnerability, infrastructural power, and political economy. Situated at the intersection of English literary studies, speculative fiction studies, ecocriticism, medical humanities, energy humanities, and sustainability discourse, the essay examines how narrative form, temporality, metaphor, and world-building render the future thinkable at human scale while keeping structural forces in view. The discussion proceeds through three major clusters. First, it reads pandemic, biotechnological, and biopolitical narratives to show that speculative literature imagines health not merely as a medical condition but as a question of care, access, reproductive justice, disability, and institutional trust. Second, it turns to climate crisis, fossil-fuel dependence, extractivism, water stress, and renewable imaginaries to show how speculative texts make energy legible as culture, conflict, and planetary infrastructure. Third, it examines labor, automation, inequality, scarcity, and post-growth possibilities to demonstrate that the genre persistently turns economic abstraction into lived experience. Throughout, the article connects these literary futures to the strategic logics of the 2030 Sustainable Development Goals, especially SDGs 3, 7, 8, 9, 10, 12, and 13. I conclude that contemporary speculative literature does not deliver policy blueprints, but it performs an equally important task: it trains ethical attention, widens political imagination, and offers narrative laboratories for more just and sustainable futures.